Assessment of patient engagement with a mobile application among service members in transition. (11th September 2015) - Pavliscsak, Holly; Little, Jeanette R; Poropatich, Ronald K; McVeigh, Francis L; Tong, James; Tillman, Johnie S; Smith, Challis H; Fonda, Stephanie Jo
Abstract: Objective: This article examines engagement with a mobile application ("mCare") for wounded Service Members rehabilitating in their communities. Many had behavioral health problems, Traumatic Brain Injury (TBI), and/or post-traumatic stress disorder (PTS). The article also examines associations between Service Members' background characteristics and their engagement with mCare. Materials and Methods: This analysis included participants who received mCare ( n = 95) in a randomized controlled trial. mCare participants received status questionnaires daily for up to 36 weeks. Participant engagement encompasses exposure to mCare, percentage of questionnaires responded to, and response time. Participants were grouped by health status—that is, presence/absence of behavioral health problems, PTS, and/or TBI. Histograms and regression analyses examined engagement by participants' health status and background characteristics. Results: Exposure to mCare did not differ by health status. Participants usually responded to ≥60% of the questionnaires weekly, generally in ≤10 h; however, participants with behavioral health problems had several weeks with <50% response and the longest response times. Total questionnaires responded to and response time did not differ statistically by health status. Older age and higher General Well-Being Schedule scores were associated with greater and faster response. Discussion: The sustained response to the questionnaires suggests engagement. Overall level of response surpassed trends reported for American's usage of mobile applications. With a few exceptions, Service Members engaged with mCare irrespective of health status. Conclusion: Mobile health has the potential to increase the quantity and quality of patient-provider communications in a community-based, rehabilitation care setting, above that of standard care.